Effect of Helicosporidium sp. (Chlorophyta; Trebouxiophyceae) infection on Cyrtobagous salviniae Calder and Sands (Coleoptera: Curculionidae), a biological control agent for the invasive Salvinia molesta D.S. Mitchell (Salviniaceae) in South - Mphephu, Tshililo Emmanuel (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
The effectiveness of established biological control agents depends on biotic and abiotic interactions in the introduced range. The weevil, Cyrtobagous salviniae Calder and Sands (Coleoptera: Curculionidae), was released as a biological control against Salvinia molesta D.S. Mitchell (Salviniaceae) in South Africa in 1985. This agent has been highly successful against S. molesta and has significantly reduced the weed's populations around the country. However, in 2007, the parasitic alga, Helicosporidium sp. (an undescribed species), was detected in field-collected C. salviniae adults in South Africa. The distribution and impacts of this disease on the weevil and its efficacy as a control agent were not known. In this thesis, the prevalence, infection load, and impact of Helicosporidium sp. on C. salviniae was determined. In 2019, adult weevils were collected from 10 sites across the Eastern Cape, KwaZulu-Natal, Limpopo, and Western Cape provinces and screened to determine the occurrence, infection load, and geographic distribution of Helicosporidium sp. Transmission mechanisms of this disease in C. salviniae were then evaluated. The possible impact of Helicosporidium sp. was assessed by comparing the feeding rates and the reproductive output of the diseased and healthy adults of C. salviniae. An attempt was then made to eliminate the disease in C. salviniae through the application of the antibiotic, ketoconazole. Further, the role of temperature on infection load in C. salviniae was also assessed. Finally, recommendations for the long-term biological control programme against S. molesta in South Africa were made. The disease covers the entire distribution range of C. salviniae in South Africa, with the disease occurrence rate ranging from 92.15% to 100% insects infected per site. Helicosporidium sp. was found to transmit vertically within the populations of C. salviniae. Infection by the Helicosporidium sp. disease reduced the reproductive output of C. salviniae as well its impact on biomass reduction of S. molesta when a diseased culture was compared to a healthy culture from the USA. 98.44 to 98.55% of Helicosporidium sp. loads were reduced through multiple applications of ketoconazole concentrations under in vitro trials. In vivo treatments resulted in 70% control of Helicosporidium sp. in the adults of C. salviniae that were fed ketoconazole three times over a 21 day period. Adult C. salviniae feeding and survival performances were similar when fed fronds of S. molesta inoculated with ketoconazole and water. The lowest and highest disease loads of Helicosporidium sp. were recorded when the weevils were reared at 30°C and 14°C, respectively. As expected, the highest impact and reproductive output of C. salviniae were at 30°C. The evaluations discussed in this thesis highlight the role of diseases in biological control agents, and gaps in both the pre-release and post-release monitoring that should integrate screening of diseases in these studies. Although the combined application of the antibiotic and temperature will reduce Helicosporidium sp. loads and impact, this technology is most likely only applicable where the weevils are reared in small numbers in a rearing facility and not really applicable to the field situation. It is important to release healthy agents that will cause efficient control of the target weed plant species, therefore, when introducing new biological control agents, the health status of such agents needs to be understood. Therefore, long-term field monitoring and assessment of the impact of C. salviniae on S. molesta should be conducted to track all the changes that may result due to the presence of Helicosporidium sp. This long-term monitoring and assessment will give a more informative role of Helicosporidium sp. in field populations of C. salviniae.
Keywords: Salvinia molesta -- South Africa; Weeds Biological control; Cyrtobagous salviniae; Ketoconazole